1997
DOI: 10.3109/10520299709082239
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid Containing Choline Histochemistry of Mouse Uterine Epithelia during Preimplantation Stage

Abstract: The physiological role of high lipid content in endometrial cells during pregnancy has not been well established. In the present work we used histochemical techniques to analyze the total lipids and phospholipid containing choline (PCC) in the mouse uterine glandular and luminal epithelia during preimplantation stage. Sudan black histochemistry showed the highest intensity during the second day of pregnancy in both the basal and apical portions of luminal epithelium. Peaks of PCC staining were seen both in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Similar to our results, LDs were detected mainly in LE but not in other uterine compartments of non-pregnant sheep [23,24]. In addition, LDs were detected in luminal and glandular epithelium, and stroma in pregnant mice [25,26], in uterine epithelium and/or stroma of non-pregnant, pregnant or ovariectomized rats [29][30][31], and in human fetal membranes and placenta at term [34,35]. Accumulation of LDs only within selected compartments of uteri and placenta indicates the specific role of LDs in endometrium.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Similar to our results, LDs were detected mainly in LE but not in other uterine compartments of non-pregnant sheep [23,24]. In addition, LDs were detected in luminal and glandular epithelium, and stroma in pregnant mice [25,26], in uterine epithelium and/or stroma of non-pregnant, pregnant or ovariectomized rats [29][30][31], and in human fetal membranes and placenta at term [34,35]. Accumulation of LDs only within selected compartments of uteri and placenta indicates the specific role of LDs in endometrium.…”
Section: Discussionsupporting
confidence: 90%
“…The specific role of LDs in uterine function has not been studied in detail, however, it has been indicated that lipid signaling is involved in preparation of the uterus for implantation [93], and that expression of LDs in endometrium is associated with prostaglandin signaling [26] and energy storage [31]. Therefore, we postulate that LDs may be involved in PG production/function/metabolism/signaling, steroidogenesis/steroid signaling, and some other processes that require additional energy sources.…”
Section: Revised 12mentioning
confidence: 95%
See 3 more Smart Citations